Ion Pair Formation of 1-Amidino-O-ethylurea Nickel(II) Chloride and 1-Amidino-O-ethylurea Nickel(II) Bromide in Aqueous Medium at Different Temperatures- A Conductance Method - Mohondas Singh, N.; Kiranjit Singh, M. (Asian Journal of Chemistry, 2012)
Aqueous solutions of 1-amidino-O-ethylurea nickel(II) chloride and 1-amidino-O-ethylurea nickel(II) bromide have been investigated at different temperatures (303-318 K) by conductance method over wide range of salt concentrations. The limiting equivalent conductances (L0) and ion association constants (KA) for various compositions have been calculated using Shedlovsky method. For both electrolytic salts, the limiting equivalent conductances increased linearly with increased in temperature and the ion association constants values increased with rise in temperature. Based on the KA values and temperature dependence of Lo, the thermodynamic parameters viz., free energy (DGº), enthalpy (DHº) and entropy (DSº) have been determined. The values of L0 for the electrolytes increase invariably with increase in temperature in aqueous medium, indicating less solvation or higher mobility of ions. This is due to the fact that the increase thermal energy results in bond breaking and leads to higher frequency and higher mobility of the ions. Values of L0 for [Ni(AEUH)2]Cl2 are always greater than those values of complex [Ni(AEUH)2]Br2. The values of the KAs for these two complexes increase with rise in temperature. The higher KA values in case of simple salt compared to complexes salt may be ascribed to the more coulombic type of interaction (specific short-range interaction) between the nickel ion and chloride ion. This is so because the charge density of [Ni(AEUH)2]Cl2 is greater than that of the charge density of [Ni(AEUH)2]Br2.